COMPETITIVENESS OF THE BANKING INSTITUTION AND ITS COMPONENTS IN MODERN REALITIES - Маринчак, Лілія Романівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The purpose of the article is to substantiate the theoretical principles of managing the competitiveness of banking institutions in the conditions of modern changes and challenges. The article highlights the key aspects affecting the competitiveness of banks, such as the economic environment, political-legal and socio-cultural environment. It is noted that in modern conditions, banks compete not only with each other, but also with non-bank financial institutions. Particular attention is paid to innovations in the banking sector, in particular digital technologies and fintech solutions that affect the management strategy of banks. Based on the analysis of domestic and foreign studies, it was established that the competitiveness of banks establishes a dynamic category that requires constant updating of management strategies and the use of the latest tools and technologies. Important factors affecting competitiveness are the economic environment, political and legal regulation, technological innovations, socio-cultural and demographic aspects. The factors of the external and internal environment that determine the competitiveness of banks are studied, and include economic and socio-cultural factors, political and legal regulation, technological innovations and management of personnel potential. It has been proven that the bank’s success in the financial services market depends on its ability to adapt to changes and implement effective management strategies aimed at ensuring the quality of customer service and using competitive advantages. Emphasis is placed on the importance of a comprehensive approach to managing the competitiveness of banking institutions, which allows them to function successfully in conditions of growing competition and difficult economic conditions. It is substantiated that an important prerequisite is constant adaptation to new realities of market relations, as well as preservation of financial stability and reliability, which forms the basis for successful competition in the conditions of global and local markets.